The Effect of Jati Belanda Leaves (Guazuma ulmifolia Lamk.) Ethanol Extract on Microscopic Features of Atherosclerotic Animal Modelâs Aorta - Permana, Ryan J.; Azaria, Cherry; Rosnaeni, Rosnaeni (Journal of Medicine and Health, 2016)
âJati Belandaâ leaves (Guazuma ulmifolia Lamk.) possesses antidyslipidemia effect and in this study we assessed the effect of "Jati Belandaâ leaves ethanol extract in delaying the progression of atherosclerosis in aorta of the rats.Thirty atherosclerosis animal models were divided into six groups, which are three variant dose of âJati Belandaâ leaves (EEDJB 1-2-3), standard control (SC), negative control (NC) and Comparative control/ CC (simvastatin). The parameters measured were the wall thickness and lumen diameter (both in mm), and the amount of foam cells. The result for Kruskal Wallis test showed highly significant differences (p=0.00) of wall thickness Dose2 (0.056 mm) and Dose3 (0.056 mm) compared to NC (0.075 mm) and non-significant compared to CC (0.055 mm). ANOVA result for lumen diameter, p=0.773.Â  ANOVA result for foam cells amount, p=0.000, Duncan test showed significantly different between EEDJB and NC group.It is concluded that âJati Belandaâ leaves ethanol extract reduced aortic wall thickness and the amount of foam cells, but did not increase lumen diameter on the athersclerotic aorta, and had an equal therapeutic effect compared to simvastatin in delaying the progression of atherosclerosis.Â Keywords: atherosclerosis, Jati Belanda, wall thickness, lumen diameter, foam cell